Dampak Tantangan dan Potensi Vibe Coding Berbasis AI dalam Lanskap Pendidikan Pemrograman: Tinjauan Literatur Sistematis - Akhmad Rezki Purnajaya (Jurnal Teknologi informasi dan Ilmu Komputer, 2026)
Vibe coding transforms natural language commands into functional code through Artificial Intelligence (AI). This Systematic Literature Review (SLR) evaluates the impacts, challenges, and potential of this approach within education. Adhering to the PRISMA protocol, 17 studies were selected based on inclusion criteria. The distribution encompasses higher education (n=9) and K-12 (n=8), focusing on tools like GitHub Copilot and ChatGPT. Synthesis results from controlled experimental studies among higher education students indicate a significant increase in task completion efficiency of up to 35%. However, a distinction is observed where increased technical productivity does not equate to improved learning achievement; instead, risks concerning diminished conceptual understanding and academic integrity challenges remain. This review is limited by the geographic dominance of studies from North America and Europe and the high heterogeneity of study designs, which necessitated a narrative synthesis. This study recommends a pedagogical shift towards critical human-AI collaboration.